UPAYA GURU TAHFIDZ DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL AL-QURAN SISWA MELALUI METODE TAKRIR DI SMP MUHAMMADIYAH 06 DAU MALANG - Muhammad Sahal; Abdul Jalil; Fita Mustafida (VICRATINA, 2022)
The purpose of this study was to describe the efforts of Tahfidz teachers to improve the students' ability to memorize the Qur'an and to describe the obstacles Tahfidz teachers had to improve the students' ability to memorize the Qur'an in SMP Muhammadiyah 06 Dau Malang. This study uses a qualitative method where data collection uses observation techniques, interviews, tests and documentation. There are 3 data analysis techniques used in this study, namely 1) Data Condensation. 2) Presentation of data. 3) and draw conclusions. The results of this study indicate that: With the implementation of the Taqrir method for Tahfidz students in SMP Muhammadiyah 06 Dau Malang, it has a positive impact on increasing the students' learning motivation, in addition to influencing the achievement of learning results. learning that increase significantly from the comparison between cycle I and cycle II. Students are also required to study independently, both individually and in groups, using various methods of learning variations. Students can explore, evaluate, interpret, synthesize, and search for information. This can be seen in the acquisition of student scores that show significant learning results, specifically in cycle I: 51.23% and cycle II: 77.55%.